Effects of Chromium Histidinate on Renal Function, Oxidative Stress, and Heat-Shock Proteins in Fat-Fed and Streptozotocin-Treated Rats - Dogukan, Ayhan; Tuzcu, Mehmet; Juturu, Vijaya; Cikim, Gurkan; Ozercan, Ibrahim; Komorowski, James; Şahin, Kazım (W B Saunders Co-Elsevier Inc, 2010)
Objective: Chromium is an essential element for carbohydrate, fat, and protein metabolism. The therapeutic potential of chromium histidinate (CrHis) in the treatment of diabetes has been elucidated. The present study investigated the effects of CrHis on serum parameters of renal function, on oxidative stress markers (malondialdehyde [MDA] and 8-isoprostane), and on the expression of heat-shock proteins (HSPs) in rats. Methods: Male Wistar rats (n = 60, 8 weeks old) were divided into four groups. Group 1 received a standard diet (12% of calories as fat). Group 2 received a standard diet, plus CrHis. Group 3 received a high-fat diet (40% of calories as fat) for 2 weeks, and was then injected with streptozotocin (STZ) on day 14 ( STZ, 40 mg/kg intraperitoneally). Group 4 was treated in the same way as group 3 (HFD/STZ), but was supplemented with 110 mu g CrHis/kg/body weight/day. Oxidative stress in the kidneys of diabetic rats was evidenced by an elevation in levels of MDA and 8-isoprostane. Protein concentrations of HSP60 and HSP70 in renal tissue were determined by Western blot analyses. Results: Chromium histidinate supplementation lowered kidney concentrations of MDA, 8-isoprostane levels, serum urea-N, and creatinine, and reduced the severity of renal damage in the STZ-treated group (i.e., the diabetes-induced group). The expression of HSP60 and HSP70 was lower in the STZ group that received CrHis than in the group that did not. No significant effect of CrHis supplementation was detected in regard to the overall measured parameters in the control group. Conclusions: Chromium histidinate significantly decreased lipid peroxidation levels and HSP expression in the kidneys of experimentally induced diabetic rats. This study supported the efficacy of CrHis in reducing renal risk factors and impairment because of diabetes. (C) 2010 by the National Kidney Foundation, Inc. All rights reserved.
Keywords: Lipid-Peroxidation; Diabetes-Mellitus; Tnf-Alpha; in-Vivo; Picolinate Supplementation; Myocardial Protection; Improves Carbohydrate; Insulin; Metabolism; Obesity